Perceived Physical Activity Benefits and Barriers in Sedentary Adults - Ieva Eva Skrebutėnaitė; Diana Karanauskienė (Lithuanian Sports University, 2019)
Background. Research aim was to analyse the perceptions of benefits and barriers of physical activity in physically inactive adults. Methods. Research methods were individual interviews and qualitative content analysis. Results. Insufficiently physically active adults have many different health and emotional problems, but this is not a sufficient motive for them to be physically active. Research participants positively evaluated the benefits of physical activity if their physical activity did not exceed their physical fitness; however, it was not optimal and did not comply with the proposed minimum recommendations. Physical activities of adults were mostly related to holidays, cooking, playing with children, and activities in nature. Meanwhile, respondents were more physically inactive - working at home, reading books, and spending time on smart devices. Adults mentioned more reasons to be physically passive than active. Internal causes of physical inactivity were related to lack of time, lack of motivation, antipathy to sport, health problems and internal beliefs, external causes - workload, weather conditions, financial situation, family and household. Conclusions. Physical health problems and psychological ailments of inactive adults were frequent consequences of physical inactivity. Their activities after work were passive (working at home, reading books and time on smart devices) and active (holidays, cooking, playing games with children, activities in nature). Although there were more active activities, most of them were in leisure time and they did not fully meet the minimum recommendations. The participants positively evaluated the benefits of physical activity if their physical activity did not exceed their physical fitness. Internal causes of physical inactivity of the participants were lack of time, lack of motivation, antipathy for sport, health problems, feeling of loneliness and age, external causes - workload, weather conditions, financial situation, family and household.